Implementation of K-Modes Clustering in Predicting Electric Power Needs in Aceh - Ula, Mutammimul; Hardi, Riyadhul Fajri; Hardi, Richki (Universitas Mulia, 2018)
The State Electricity Company is tasked with providing a stock of electricity power grouping requirements and classification of classifications for each region in the city of Aceh. The area to be grouped is based on the amount of power consisting of four sub-districts namely Banda Sakti, Blang Mangat, Muara Dua and Muara Satu, each of which comes from Gampong. The importance of clusters to separate each data between gampong data that will be entered into each sub-district. Furthermore, the K-Means Clustering Classification is used in determining the grouping of electric power needs in each region in Aceh City, where the system classifies the electricity stock requirements in each region categorized into a clustering.